(untitled) (International Journal of Physiotherapy, 2025)
Background: Osteoarthritis (OA), a degenerative joint disease, is exacerbated by obesity. High-intensity interval Training (HIIT) offers potential benefits for obese individuals with OA by improving fitness while reducing joint impact. Methods: This study evaluated the effects of an 8-week HIIT program on Body Mass Index (BMI), pain levels, functional mobility, and lipid profiles in obese females (40-60 years) with early-stage OA. Participants underwent pre- and postintervention assessments using the Visual Analog Scale (VAS), Timed Up and Go (TUG) test, and lipid profile analysis. Results: Post-intervention, participants experienced significant improvements in pain levels (VAS scores, p≤0.005) and functional mobility (TUG test, p≤0.005). However, lipid profiles showed no significant changes. Conclusion: HIIT demonstrates promise in reducing pain and enhancing mobility among obese females with early stage OA, though its effects on other health risks require further investigation.